Junior secondary school student's competency in ICT: an assessment of effectiveness of SNNG project in southwest, Nigeria (2007)
Identifying effective and ineffective schools is a dominant issue in education in light of the increasing concern for student's achievement , performance and accountability. Educators involved in school improvement projects face the dilema of choosing from a variety of methods for measuring school effectiveness. One of such methods to improve learning and teaching in Nigeria is not to undermine the impact of ICT in junior secondary schools as well as their ability to show level of competence in ICT . This study therefore examined the junior secondary schools studetns' competence in ICT aspect of computer education. Purposive sampling sampling techniques was used to select the schools involved in the study . The sample consist of 562 (51.1%) males and 538 (48.9%) females. The students were between 12 and 17 years old. Students' competence in ICT test was used to measure their ability in computer education. Data were analysed using descriptive statistics and multiple regression. The results shown that 31.1% scored above average, while 68.9% scored below average. There was a significant composite effect iof access, utilization and quality of ICT facilities on competence (F(8,1091)=7.74, p<0.05). The most predictors of students' competence in ICT were access to computer, quality of internet and hours student spent on internet to do homework. It is recommended that there is need to increase students' access, utilization and quality of ICT facilities because of improved students' competence in ICT usage. Therefore, there is need to maintain the qualities of ICT facilities in the existing schools and extend its provision to other schools so as to enhance school effectiveness. More time should be given to develop skills in computer education so as to master necessary competence in ICT.